3D 점 데이터 그리딩을 위한 고성능 병렬처리 기법 - 이창섭; 이희진; 오상윤; Lee, Changseop; Rizki, Permata Nur Miftahur; Lee, Heezin; Oh, Sangyoon (정보처리학회논문지. KIPS transactions on computer and communication systems 컴퓨터 및 통신 시스템, 2014)
3D point data is utilized in various industry domains for its high accuracy to the surface information of an object. It is substantially utilized in geography for terrain scanning and analysis. Generally, 3D point data need to be changed by Gridding which produces a regularly spaced array of z values from irregularly spaced xyz data. But it requires long processing time and high resource cost to interpolate grid coordination. Kriging interpolation in Gridding has attracted because Kriging interpolation has more accuracy than other methods. However it haven't been used frequently since a processing is complex and slow. In this paper, we presented a parallel Gridding algorithm which contains Kriging and an application of grid data structure to fit MapReduce paradigm to this algorithm. Experiment was conducted for 1.6 and 4.3 billions of points from Airborne LiDAR files using our proposed MapReduce structure and the results show that the total execution time is decreased more than three times to the convention sequential program on three heterogenous clusters. 3D 점 데이터는 높은 정확성을 가진 사물의 표면 정보 데이터로 다양한 분야에서 사용되고 있으며, 특히 지리학에서 지형 파악과 분석에 많이 사용되고 있다. 일반적으로 3D 점 데이터의 Gridding 과정을 거치게 되는데 이는 불연속적인 점 데이터를 일정한 좌표 값으로 만드는 과정으로 긴 실행 시간과 높은 비용이 필요하다. 특히 Gridding 과정 중 보간 작업을 위해서 Kriging이 높은 정확성으로 주목받고 있지만 처리과정이 복잡하고 연산이 많아 처리속도가 상대적으로 느리기 때문에 많이 사용되지 않고 있다. 본 논문에서는 Gridding을 고성능으로 처리하기위해 Kriging 연산 과정을 병렬화했으며 격자 자료구조를 MapReduce 패러다임에 맞게 변형하여 Kriging에 적용하였다. 실험은 항공 LiDAR 데이터 약 1.6백만 개와 4.3백만 개의 점 데이터를 이용해서 제안한 MapReduce 구조에 적용하였고, 그 결과 3대의 이기종 클러스터에서 전체 실행시간이 순차적 프로그램에 비해 최대 3.4배 단축하였다.